A Multi-Country Comparison of the Efficiency of the German Telecommunications Industry - Georg Erber (Weekly Report, 2005)
In an international comparison of the efficiency of the telecommunications (TC) industry for the period 1981 to 2002 Germany is in a middle position; France and Great Britain are better, while the Netherlands and the United States are in a less favourable position. However, supply-side efficiency is subject to strong fluctuations over time. Germany's TC industry suffered a temporary slump in efficiency compared with the other countries during deregulation, and this could only be made up again gradually from 2000. For a time Germany was actually bottom of the list, but in 2001 it had moved up again to fourth place. The fluctuation can be interpreted in this way: Germany undertook the structural reforms needed to increase efficiency in the TC industry later than other countries, and the first signs of success only appeared after 1999, the year of the low. In this analysis the stochastic possible production frontiers (SPFs) method is used for the first time in a multi-country comparison of the TC industry. The advantage of this method over others is that it is based on a well-founded theoretical concept of production.
Keywords: 330